Morphological variability in Adesmia latifolia population - Scheffer-Basso, Simone Meredith; Weber, Fernanda; Dall’Agnol, Miguel; Lubenow, Ricardo (Agrociencia Uruguay, 2003)
Adesmia latifolia is a wild legume of Southern Brazil pastures, for which there is no information about either its morphological variability or descriptor list. The objective of this study was to evaluate the similarity amongst five population collected at different altitudes in Rio Grande do Sul and Santa Catarina: 1350 m (ALU1, ALU2), 884 m (ALL), 212 m (ALB) and 444 m (ALC). The morphology of stolons, leaves, inflorescences, fruits and seeds was evaluated. The data were submitted to multivariate analysis. The inflorescence length was the trait with the highest relative contribution to genetic divergence (36%), followed by the seed number/fruit (25%). According to Mahalobis' distance, the ALU1 and ALU2 population showed the lowest distance; the highest distance was between ALL and ALB. The ALB population showed the biggest genetic divergence in relation to the others. The existence of variability shows the importance of enlarging the species collection to identify morphological types with yield characteristics that would be useful in breeding program for the species.